2016
DOI: 10.1016/j.gene.2016.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Progestin-mediated activation of MAPK and AKT in nuclear progesterone receptor negative breast epithelial cells: The role of membrane progesterone receptors

Abstract: Progesterone (P4), a steroid produced during estrous cycles and gestation for maintenance of pregnancy, also plays key roles in breast development to allow lactation post-parturition. Progestins (P4 and related steroids) are also implicated in breast cancer etiology. Hormone replacement therapy containing both estrogen and progestins increases breast cancer incidence while estrogen hormone therapy lowers breast cancer risk. P4 signaling via nuclear P4 receptors (PRs) has been extensively studied in breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…MDA-MB-231 cells lack the classical nPR [ 6 ], while these cells express a less characterized and alternatively spliced nPR, which may also bind to P 4 [ 23 ]. Additionally, the effect of P 4 in cell proliferation has been shown to be different according to the cell types investigated [ 6 , 8 , 24 ]. As previously reported [ 6 ], and as depicted in Figure 1 A, the treatment of MDA-MB-231 cells with 1 μM of P 4 resulted in a significant reduction of bromodeoxiuridin (BrdU) fluorescence at all analyzed times (24–72 h), as compared to cells treated with the vehicle.…”
Section: Resultsmentioning
confidence: 99%
“…MDA-MB-231 cells lack the classical nPR [ 6 ], while these cells express a less characterized and alternatively spliced nPR, which may also bind to P 4 [ 23 ]. Additionally, the effect of P 4 in cell proliferation has been shown to be different according to the cell types investigated [ 6 , 8 , 24 ]. As previously reported [ 6 ], and as depicted in Figure 1 A, the treatment of MDA-MB-231 cells with 1 μM of P 4 resulted in a significant reduction of bromodeoxiuridin (BrdU) fluorescence at all analyzed times (24–72 h), as compared to cells treated with the vehicle.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated PGRMC1 and downregulated ATP1A1 both enhance AKT phosphorylation in RCC cells. PGRMC1 promotes activation of the PI3K/AKT signaling pathway (4,32). On the other hand, inhibitors of Na + /K + -ATPase can activate PI3K/AKT signaling pathways (33).…”
Section: Resultsmentioning
confidence: 99%
“…The activation of the PI3K-AKT signaling pathway has been shown to play an important role in many cancer types (34). Several studies suggest that progesterone accumulation could promote AKT phosphorylation in breast epithelial and ovarian cancer cells (4,32). PGRMC1 knockdown can reduce phosphorylation of certain downstream EGFR targets, including AKT and ERK in HCT-116 cells (8).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, C6 cells have also been shown to express mRNA for the membrane progesterone receptors (mPR; Su et al, 2012a). Salazar et al (2016) demonstrated MPA elicits progestin-induced intracellular signaling in PR-negative breast epithelial cells, suggesting a potential mode of action via membrane progesterone receptors. Possibly, our observations may be partially due to non-genomic signaling through membrane progesterone receptors, however, there is currently a lack of information regarding MPA's relative binding affinity to membrane progesterone receptors and a lack of evidence relating to MPA's propensity to elicit its effects via non-genomic membrane-bound signaling.…”
Section: Discussionmentioning
confidence: 95%